2016
DOI: 10.1016/j.jcv.2016.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Serologic evidence for hepatitis E virus infection among patients with undifferentiated acute febrile illness in Kibera, Kenya

Abstract: Background Hepatitis E (HEV) is an emerging cause of viral hepatitis mainly transmitted through the fecal-oral route. Residents of the Kibera slum of Nairobi, Kenya are at risk for fecal-orally transmitted infections. Objective To quantify the incidence and prevalence of HEV infection among acute febrile illness (AFI) cases using a population-based infectious disease surveillance network. Study Design Cross-sectional serum samples from AFI case-patients between 2009 and 2012 were matched to the age and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
(26 reference statements)
2
13
0
Order By: Relevance
“…Of the studies in the general population, 7 were on blood donors with IgG seroprevalence ranging from 4.6–47.8%. IgM seroprevalence and therefore risk of HEV contaminated donor blood was 3.1–5.9% [ 53 , [60] , [61] , [62] , [63] , [64] ]. Also, 3 of the studies were from Burkina Faso which showed a significantly higher prevalence than other countries increasing over time (19% in 2012 to 40% in 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the studies in the general population, 7 were on blood donors with IgG seroprevalence ranging from 4.6–47.8%. IgM seroprevalence and therefore risk of HEV contaminated donor blood was 3.1–5.9% [ 53 , [60] , [61] , [62] , [63] , [64] ]. Also, 3 of the studies were from Burkina Faso which showed a significantly higher prevalence than other countries increasing over time (19% in 2012 to 40% in 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In 2 cohort studies, no significant difference was reported in HEV prevalence between people with and without HIV [ 90 , 91 ]. In contrast, both Furukawa et al [ 64 ] and Jacobs et al [ 82 ] found that HIV infection significantly increased the likelihood of HEV infection. Caron et al [ 72 ] found that HIV viral load was significantly higher in pregnant women testing positive for anti-HEV IgG (1.3E+05 vs 5.7E+04 copies per ml; p ≤ 0.02).…”
Section: Hiv Patientsmentioning
confidence: 96%
“…Data on risk factors for HEV infection (defined by IgM antibodies or RNA), disease, and death were identified in 36 studies (17,21,26,30,34,46,63,68,74,85,91,92,102,104,(108)(109)(110)112,116,129,138,139,(145)(146)(147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158) from 13 countries between 1990 and 2017. One study only reported risk factors with an unknown hypothesized direction of effect and was excluded from further analysis (159).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Transmission of HEV primarily occurs by the fecal-oral route via contamination of drinking water and food supplies [3]. Parenteral as well as vertical transmission may also occur particularly in endemic regions; however person to person transmission is uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…Journal of Biosciences and Medicines 37.8% (IgG)[3]. It would be expected that healthy blood donors would have a lower seroprevalence compared to febrile patients since HEV is a known cause of febrile illness.…”
mentioning
confidence: 99%